Tradable Refugee-Admission Quotas and EU Asylum Policy - Jesús Fernández-Huertas Moraga; Hillel Rapoport (Institute for the Study of Labor (IZA), 2014)
The current EU Asylum policy is widely seen as ineffective and unfair. We propose an EU-wide market for tradable quotas on both refugees and asylum-seekers coupled with a matching mechanism linking countries' and migrants' preferences. We show that the proposed system can go a long way towards addressing the shortcomings of the current system. We illustrate this claim using the recent problems regarding relocation faced by the European Relocation from Malta (EUREMA) program.
Keywords: F22; F5; H87; I3; K33; O19; 330; asylum seekers; refugee resettlement; tradable quotas; EU policy; immigration policy; international public goods